UPAYA MENINGKATKAN DAYA SAING PEDAGANG KAKI LIMA DIKAWASAN PARIWISATA PANTAI PANJANG KOTA BENGKULU - Ahmad Farhan Febrian S.Z; Islamuddin Islamuddin (UM. Bengkulu, 2026)
This study aims to examine efforts to improve the competitiveness of street vendors (PKL) in the Panjang Beach tourism area, Bengkulu City, using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis approach. Panjang Beach is a prime tourist destination frequented by both domestic and international tourists. However, street vendors in this area face various challenges such as limited facilities, intense competition, limited capital, and a lack of promotional skills and technology utilization. This study used a descriptive qualitative approach, collecting data through interviews with six informants: four street vendors and two tourists. The analysis shows that the main strengths of street vendors are their strategic location, good product quality, and customer loyalty, while their weaknesses lie in limited capital, poor marketing knowledge, and suboptimal time management. Opportunities that can be exploited include evolving market trends and technological advances, while threats stem from intense competition, fluctuating raw material prices, and uncertain government policies. Based on the IFAS and EFAS Matrices, street vendors' strategic position is in quadrant II (diversification), with coordinates (0.65; -0.20), indicating the need to leverage internal strengths to address external threats. Keywords: street vendors, competitiveness, diversification strategy, SWOT analysis